Manejo de inventario en el departamento de bodega de la Empresa Grusepe S.A. - Alvarado Rodríguez, Úrsula Amarilis (2020)
In the present case study, the problems that arise in the control and management of the accounting item of inventories of the company GRUSEPE S.A., are investigated and recognized, this being an organization that is dedicated to providing services related to medical analysis in clinical laboratories to the inhabitants who are within the locality of economic operation and nearby cities; There are conditions that arise in this organization, the application of an untrue administration, because they do not have a human talent trained in the development of administrative and accounting activities, a transcendental origin that influences the weaknesses that arise in inventory management. The control and registration of goods and materials of the organization is carried out in a conventional way, subject to unreliable data imparted by collaborators of the health area who perform in the respective laboratories, without the coupling of necessary tools for the proper registration of entry and exit assets, a situation that has caused the decision-making process to be inadequate, due to ineffective inventory control affecting the financial management of the institution. The case study is structured through descriptive research and the use of the inductive method, it is obtained as results that the organization does not use the use of a weighted average method efficiently for inventory control, where inventory management It is inappropriate due to the work profile of the organization's collaborators.